Transport Corridors as a Social-Economic Energizer - Qaja, Besjana (European Journal of Multidisciplinary Studies, 2020)
Transport corridors and their socio-economic impact have been analyzed and explored in many cases. In the transport sector, there is a series of problems that affect the quality of life of the inhabitants in different regions. These issues need to be analysed and to find the cause and consequences that they cause and hinder the further development of the region initially and subsequently affect the national level. Moreover, roads as a construction structure have a very important role in the economic development of a country. They enable quick and convenient transportation of people to settlements as well as the economical transport of goods. The geographical position of the places, the natural beauties, and the sea are a prerequisite for tourism development. But in many cases, the natural and attractive attractions for tourists remain unused due to the lack of roads or the existence of a poor road network. The inspiration for the development of this topic comes from the daily observation of the transport situation and from receiving information through various publications such as studies, strategies or thematic books, discussions with colleagues and various events related to this sector. The research is focused on a specific case that can combine the theoretical part with the real situation to confront them both between using a specific methodology. The aim of this paper is to extract some of the reasons for regional development and energizing. As a case study is taken a part of route 7, in the Balkan peninsula which connects Albania with Kosovo and Serbia. Discussions on the construction of a highway between Albania and Kosovo are early, they were born on the eve of the First World War in Austria-Hungary. Even in the 1970s and 1980s, there was a discussion about building a road that would have to connect two locations. Based on this, it looks a good reason to search more and to analyse some effects of it in the social and economic life of citizens and residents of the impacted areas.